Contributing Environmental Factors of Habitat Suitability for the Great Argus (Argusianus argus) in Bukit Barisan Selatan National Park, Indonesia - Rahmilija, Femei; Hernowo, Jarwadi Budi; Prasetyo, Lilik Budi (Jurnal Manajemen Hutan Tropika, 2026)
The great argus (Argusianus argus), a key outstanding universal value (OUV) species in Bukit Barisan Selatan National Park (BBSNP) within the tropical rainforest heritage of Sumatra (TRHS), is listed as vulnerable by the IUCN red list due to extensive deforestation and habitat fragmentation. Yet, its habitat preferences and spatial distribution remain poorly understood. This study aimed to model the potential distribution of the great argus and identify key environmental factors influencing its occurrence within the Way Canguk Research Station (WCRS), BBSNP. We employed the Maximum Entropy (MaxEnt) algorithm using data from field surveys and camera traps combined with environmental variables including elevation, slope, distance to rivers, normalized difference moisture index (NDMI), temperature, rainfall, distance to roads and settlements, NDVI, and land cover. The model exhibited high predictive performance (AUC = 0.846). Distance to roads, rainfall intensity, and the presence of primary forest emerged as the most influential factors. The species showed a preference for primary forests located far from human disturbances and in areas with lower rainfall levels. These findings confirm WCRS as a suitable habitat for the great argus and underscore the urgency of preventing deforestation, restoring degraded lands, and mitigating road impacts to preserve BBSNP’s ecological integrity and sustain TRHS’s world heritage status.